Handbook of student engagement interventions : working with disengaged students - Fredricks, Jennifer A.; Reschly, Amy L.; Christenson, Sandra L. (Academic Press, 2019)
Handbook of Student Engagement Interventions: Working with Disengaged Students provides an understanding of the factors that contribute to student disengagement, methods for identifying students at risk, and intervention strategies to increase student engagement. With a focus on translating research into best practice, the book pulls together the current research on engagement in schools and empowers readers to craft and implement interventions. Users will find reviews on evidence-based academic, behavioral, social, mental health, and community-based interventions that will help increase all types of engagement. The book looks at ways of reducing suspensions through alternative disciplinary practices, the role resiliency can play in student engagement, strategies for community and school collaborations in addressing barriers to engagement, and what can be learned from students who struggled in school, but succeeded later in life. It is a hands-on resource for educators, school psychologists, researchers, and students looking to gain insight into the research on this topic and the strategies that can be deployed to promote student engagement.